Camellia sinensis and Phyllanthus amarus ethanol extracts induced apoptosis and cell cycle arrest on human leukemic cell lines - Syaratul Dalina Yusoff,; Endang Kumolosasi,; Mursidah Md Ali,; Yap, Ren Qian; Norsyahida Mohd. Fauzi,; Affidah Sabran, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Leukaemia is a heterogeneous hematologic malignancy characterized by unregulated proliferation of the early blood-forming cells which starts in bone marrow. The basic strategy of leukaemia therapy involves the induction of leukemic cells apoptosis. Research on natural products have shown that some plant derivatives have anticancer properties by inducing apoptosis of leukemic cells. Plants such as Camellia sinensis and Phyllanthus amarus are those that had gained a wide interest due to their anti-cancer effect. The aim of this study was to investigate the anti-cancer effects of C. sinensis and P. amarus extracts on human leukemic cell lines by analysing the cell cycle and determining the apoptotic state. The cell lines were treated with ethanolic plant extracts at the concentrations of 31.25 - 500 µg/mL for 24 h followed by MTT assay to determine the IC50. The IC50 of C. sinensis and P. amarus on the U937 cells were 170±10.39 and 210±6.78 µg/mL, respectively. Flow cytometric analysis of apoptosis using Annexin V/propidium iodide (PI) staining was also performed. C. sinensis extract at 170 µg/mL significantly increase apoptosis in U-937 (p<0.001), Jurkat (p<0.05) and K-562 cells (p<0.01) when compared to untreated cells. Meanwhile, P. amarus extract at 210 µg/mL significantly induced apoptosis in both U937 and K562 cells (p<0.05) but not Jurkat cells and caused cell cycle arrest at S phase in U-937 cells (p<0.001) and at G0/G1 in K652 cells (p<0.05) when compared to control. Based on the findings, both C. sinensis and P. amarus extracts showed potential in inducing apoptosis in human leukemic cell lines. In addition, P. amarus has the capability to disrupt cell cycle.